Comparative Analysis of the Performance of SQL and NOSQL DBMS - Новиков, Борис Асенович; Левин, Максим Юрьевич (Computer Tools in Education, 2017)
NoSQL database management systems have been under examination by industry specialists for quite some time. However, at the moment there are very few works connected with this topic, and in particular - with the comparison of such systems with traditional relational DBMSs. As for the existing studies, some articles are plain overviews, some use a small number of records in tables as a workload or they only consider one environment for conducting experiments, which can give advantage to one of the comparison objects. This paper is concerned with PostgreSQL and MongoDB. The first system, despite being free and open-source software, is rapidly gaining popularity even in the corporate world, whereas the second one differs from a large number of NoSQL solutions in its meticulousness and support. In order to ensure the completeness of the comparison, the experiments were carried out in different environments and with different loads.